FAKTOR-FAKTOR YANG MEMENGARUHI MINAT BERWIRAUSAHA MAHASISWA BIDANG AGRIBISNIS MAHASISWA UNIVERSITAS BATURAJA - Ratusina, Mutiara; Lastinawati, Endang; Septianita, Septianita (Universitas Galuh, 2023)
This study aims to determine the factors that influence the interest in entrepreneurship in the agribusiness field of Baturaja University students. This research method was carried out using quantitative methods in which the research used binary logistic regression analysis. Data was obtained by distributing questionnaires and data obtained from students of Agribusiness and Management at Baturaja University. The results of this study are the factors that influence the interest in entrepreneurship in the agribusiness field of Baturaja University students, namely there are four factors, namely capital, number of family members, pocket money and income expectations. All of these four factors have a significant effect on the interest in entrepreneurship at Baturaja University students.